GHEP-ISFG proficiency test 2011: Paper challenge on evaluation of mitochondrial DNA results - Prieto, L. (2013)
The GHEP-ISFG Working Group performed a collaborative exercise to monitor the current practice of mitochondrial (mt)DNA reporting. The participating laboratories were invited to evaluate a hypothetical case example and assess the statistical significance of a match between the haplotypes of a case (hair) sample and a suspect. A total of 31 forensic laboratories participated of which all but one used the EMPOP database. Nevertheless, we observed a tenfold range of reported LR values (32–333.4), which was mainly due to the selection of different reference datasets in EMPOP but also due to different applied formulae. The results suggest the need for more standardization as well as additional research to harmonize the reporting of mtDNA evidence.